Integrating Forecast Models into Business Intelligence Solutions: A Case Study on Retail Dataset - Nguyen Phat , Dat; Nguyen Van , Ho; Le Ba, Thien; Trinh Thu Huyen , Trang; Lam Thi Hoang , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Business Intelligence (BI) is a collection of solutions for collecting, managing, and exploiting data to support decision-making in enterprises. In recent years, this solution is gradually becoming popular and applied by many businesses based on the “accumulation” of data over time. However, current business intelligence solutions are restricted to descriptive statistics, the use of forecasting models are still limited due to the complexity of integration, cost, as well as specialized capacity. subjects related to machine learning models. Since then, this study has formed a solution to integrate predictive models into business intelligence solutions, experimenting on retail data sets, and focusing on small and medium-sized companies to optimize costs and ease. deployment. The results from the study have four main contributions, including (1) Helping administrators to structure, arrange and organize data according to Business Functions; (2) Helping administrators have an overview of the operation of the business from detailed to overview; (3) Helping managers make the right decisions, business strategies, quickly, timely and accurately; (4) Helping administrators easily integrate predictive models into business intelligence solutions. This solution is completely suitable and can be applied to businesses with sales data tracking.
Keywords: Forecast Model; Retail Dataset; Management Information System; Support Decision-making; Business Intelligence; Data Analysis